Functional state of the cardiovascular system of the students of a special medical group (Experimental biology, 2016)
The main objective of a course of medicalphysical training in higher education institution is harmonious development, health promotion and working capacity increase.Functional state of the cardiovascular system of the students of a special medical group was considered in this article.The article reflects the effect of therapeutic physical training on cardiac hemodynamics of the main parameters (systolic blood volume, minute blood volume) and heart rate. The results of indexes of cardiac hemodynamics (systole and minute volume of blood), frequency of breathing and frequency of heart-throbs are examined in the article. It is set that during a semester there is an insignificant increase of indexes at different groups on the different parameters of cardiac hemodynamics, frequencies breathing and on frequency of heart-throbs.
Keywords: students; state of health; functional tests; therapeutic physical training; frequency of heart-throbs; systolic volume; myopia; cholecystitis; pyelonephritis; mitral valve prolapsed